Sosialisasi Anti-Bullying dan Penguatan Nilai-Nilai Pancasila di SD Negeri 7 Mawasangka Timur - Al Jum'ah, Muhammad Naim; Syukur, Abdul; Rizmaya, Rizmaya; Fatmawati, Fatmawati; Syaiful, Syaiful; Fauzia, Fauzia; Asiari, Asiari; Ismail, Ismail; Yusuf, Muhammad; Ardin, Ardin; Fazira, Yuli; Amir, Alya; Amlis, Muh. Ferdin Al Rizky; Gemilang, Pices Fernama (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Bullying in elementary schools is a serious issue that can hinder children’s psychological and social development. This community service activity aimed to provide early understanding of the negative impacts of bullying while instilling the values of Pancasila as the foundation of character building. Thus, students are expected to be able to reject all forms of bullying behavior and internalize the values of humanity, unity, and justice in their daily lives. The implementation method was carried out through a participatory educational approach, including interactive lectures on the forms and impacts of bullying, group discussions that allowed students to share views and experiences, role-playing to practice the courage to reject bullying, and the use of educational media in the form of posters and visual presentations. Evaluation was conducted through observation of student attitudes and simple questionnaires to measure their level of understanding. The activity was attended by 45 students from grades IV to VI, divided into discussion groups. The results showed a significant increase in students’ understanding. As many as 80% of students were able to mention at least three forms of bullying, 70% demonstrated the courage to reject bullying behavior through role play, and most students understood the application of humanity, unity, and justice values in daily practice. In addition, teachers felt supported by the socialization material and planned to integrate it into classroom learning. This activity concludes that strengthening Pancasila values through anti-bullying socialization can increase awareness and shape students’ attitudes to create a safer and more inclusive school environment. This model of activity presents a new approach to character education by actively involving students and emphasizing the engagement of the school community.